2012
DOI: 10.1051/0004-6361/201117383
|View full text |Cite
|
Sign up to set email alerts
|

Spectra probing the number ratio of C- to M-type AGB stars in the NGC 6822 galaxy

Abstract: Aims. We calibrate spectroscopically the C-versus (vs.) M-type asymptotic giant branch (AGB) star selection made using near-IR photometry, and investigate the spatial distribution of the C/M ratio in NGC 6822, based on low resolution spectroscopy and near-IR photometry. Methods. We obtained low resolution multi-object spectroscopy with the VIMOS instrument at the ESO VLT of ∼800 stars in seven fields centred on NGC 6822. The spectroscopic classification of giant stars in NGC 6822 and foreground dwarf contamina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(83 citation statements)
references
References 55 publications
9
74
0
Order By: Relevance
“…All three regions were compared with the chosen library spectra where possible. The standard spectra used for comparison were selected from the libraries of Danks & Dennefeld (1994) and Kacharov et al (2012), both of which can be obtained through the VizieR database.…”
Section: Automated Spectral Classificationmentioning
confidence: 99%
See 3 more Smart Citations
“…All three regions were compared with the chosen library spectra where possible. The standard spectra used for comparison were selected from the libraries of Danks & Dennefeld (1994) and Kacharov et al (2012), both of which can be obtained through the VizieR database.…”
Section: Automated Spectral Classificationmentioning
confidence: 99%
“…The spectral library of Kacharov et al (2012), which contains spectra of 546 sources at a resolution of 12-13 Å in the wavelength range of 5000-10 000 Å was particularly useful, as it is the largest spectral library of AGB sources in NGC 6822. It includes M-type giants of subclass M, M0, M0.5, M1, M2, M3, M4, M5, M6 and M6.5, S-type giants of subclass S0 and S4, and C-type giants of subclass C, C3.2, C5.5, C6.5 and C8.2; as well as foreground K-type (dK, dK7) and M-type (dM, dM0, dM1, dM1.5, dM2, dM3, dM3.5, dM4, dM4.5, dM5, dM6) dwarf stars in the direction of NGC 6822.…”
Section: Automated Spectral Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that spectroscopic data are necessary for a more accurate identification of M-giant and C stars. However, Battinelli & Demers (2009) discussed that many C stars probably have a bluer color than the (J − K) 0 = 1.4 limit, and Kacharov et al (2012) indeed found in their spectroscopic data of NGC 6822 that several of the C stars in NGC 6822 have a bluer color than this limit. Thus, our color limit for the C stars is reasonable compared with the other conditions.…”
Section: Color−color Diagrams and The Selection Of The C Stars Of Ic mentioning
confidence: 96%